2017
DOI: 10.1002/adsc.201700774
|View full text |Cite
|
Sign up to set email alerts
|

Ruthenium on Carbon Catalysed Carbon‐Carbon Cleavage of Aryl Alkyl Ketones and Aliphatic Aldehydes in Aqueous Media

Abstract: A new ruthenium on carbon-catalysed carbon-carbon (CÀC) cleavage reaction of aryl alkyl ketone derivatives in water in the presence of CaO under atmospheric oxygen conditions has been developed. Corresponding benzoic acid derivatives were produced from various aryl alkyl ketones in excellent yields. CaO acts as an adsorbent of CO and CO 2 to maintain a sufficient concentration of oxygen around the catalyst required for effective progress of the reaction. It was also revealed that aliphatic aldehydes were gener… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…When the oxygen pressure was 0.5 MPa, 83% yield was observed (Table 1, entry 2), while no benzophenone product was obtained under the oxygen-free condition (Table 1, entry 12), suggesting that oxygen was essential. When the pressure of oxygen increased from 0.5 MPa to 1, 2 or 4 MPa, both the conversion and the yield significantly decreased (Table 1, entry 2 vs entries [15][16][17], which revealed that 0.5 MPa was the optimal pressure.…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…When the oxygen pressure was 0.5 MPa, 83% yield was observed (Table 1, entry 2), while no benzophenone product was obtained under the oxygen-free condition (Table 1, entry 12), suggesting that oxygen was essential. When the pressure of oxygen increased from 0.5 MPa to 1, 2 or 4 MPa, both the conversion and the yield significantly decreased (Table 1, entry 2 vs entries [15][16][17], which revealed that 0.5 MPa was the optimal pressure.…”
Section: Resultsmentioning
confidence: 98%
“…It has been reported that FeCl 3 has the ability to catalyze this transformation (Scheme 1a). [14] Other transition metal catalysts include Mn, [15] Au, [16] Ru, [17] and Rh [18] compounds. Recently, several transition metal-free methods have also been developed using base [19] or other [20] as the promoters.…”
Section: Introductionmentioning
confidence: 99%